Costumbres y tradiciones para promover el rescate de la identidad cultural en la parroquia Santiago, cantón Loja. - Correa Toledo, Helen Antonela (2024)
The present investigative work was carried out with the objective of analyzing the customs and traditions of the residents of the rural Santiago parish, to promote the rescue of cultural identity. To do this, the need to create a digital channel on the YouTube platform was considered, since there is the importance of showing the reality of a people that still keeps alive certain customs and traditions inherited from their grandparents, maintaining the idea that this can be preserved for future generations, images of the daily life of the community will be used, where a society full of customs and history is highlighted, in order to publicize and contribute to the subsistence of the cultural and social heritage of the ancestral peoples. In order to achieve an adequate study of this culture, an analysis of Andean culture and knowledge was carried out, for which different authors were investigated. The mixed method was used for the development of the research, since it is related to the qualitative and quantitative method, based on field methodologies and investigative instruments such as: ethnography in communication, interviews and surveys, information that allowed us to have a broader perspective of the different cultural and symbolic expressions of the community. The participatory method of its inhabitants is also used, so that it is the one that provides adequate information on relevant data in order to enrich the digital channel. The field visit is essential to be able to know and observe everything that the place offers, and we can conclude that it is essential to design the digital channel on YouTube to 'enhance the revaluation of the cultural identity in this town. Keywords: culture, symbolism, traditions, ancestral peoples, digital channel.